Efficacy and safety of platelet-rich plasma combined with Tai Chi for knee osteoarthritis: study protocol for a placebo-controlled randomized trial - Kun Yang; Yuwu Ding; Haichen Xu; Minghui Lai; Xueping Xu; Xiaoming Yu; Qian Deng; Liming Jiang (Journal of Orthopaedic Surgery and Research, 2023)
Abstract Background No definitive treatment methods of curative for knee osteoarthritis (KOA). The combined therapies that into account both the biochemical and biomechanical may provide potential opportunities for treat KOA, and previous studies have demonstrated that the platelet-rich plasma of intra-articular injection (IAI-PRP) and exercise treatments afford more benefits than do their corresponding monotherapies. The absence of a specific exercise plan and detailed explanation renders the aforementioned study results questionable. Furthermore, Tai Chi (TC) with moderate-intensity, whole body movements and good adherence may prove to be more effective for treating KOA. However, few studies examined the effectiveness and safety of combined IAI-PRP and TC for KOA. Methods This study protocol will be a placebo-controlled, assessor-blinded randomized trial involving 12-week intervention and 1-year follow-up. The stratified randomization will be used to randomly assign the 212 participants to four groups: group A (placebo IAI); group B (PRP IAI); group C (TC and placebo IAI); group D (TC and PRP IAI). Injection will be performed once a week, three consecutive times as a course, after a week of rest to continue the next course, a total of 3 courses (12 week). Additionally, the TC interventions will be carried out 3 days per week for a total of 12 weeks. The primary outcome measures will include the efficacy (Western Ontario and McMaster Universities Osteoarthritis Index), acceptability and safety of these interventions. The secondary outcome measures will include physical function (Timed Up and Go test), walking function (Gait Analysis), inflammatory factor levels (e.g., Interleukin-1 β, interleukin-6, vascular endothelial growth factor), quality of life (36-Item Short Form Health Survey), volume of patellofemoral cartilage and effusion-synovitis (MRI). Two-way of variance with repeated measures will be applied to examine the main effects of the group and the time factor and group-time interaction effects for all outcome measures. Discussion This trial will be first one to propose an integrated scheme combing IAI-PRP and TC for treatment of KOA, based on the consideration of the biochemical and biomechanical pathogenesis of KOA. These results of the study will provide evidence with high quality for integrated IAI-PRP and TC to treatment KOA. Trial Registration Chinese Clinical Trial Registry ChiCTR2300067559. Registered on 11 January 2023.